2003
DOI: 10.1207/s15326942dn2401_01
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Verbal Long-Term and Working Memory Performance Reveal Deficits in Strategic Processing in Children With Frontal Infarcts Related to Sickle Cell Disease

Abstract: Frontal brain regions are thought to mediate strategic processes that facilitate memory. We hypothesized that children with frontal cerebral infarcts related to sickle cell disease (SCD) would exhibit impairments in long-term and working memory as a result of disruptions in strategic processing. Word-list learning and digit span tasks were used to assess verbal memory and strategic processing in 21 children with SCD without infarcts (controls) and in 10 children with SCD with frontal infarcts. On the word-list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
2
24
1
1
Order By: Relevance
“…Most researchers investigating executive functions of children with SCD focused on mental flexibility and sustained attention, overlooking other relevant frontal lobe functions such as response inhibition and planning [9][10][11][12]34]. The results of the present study failed to find support for deficits in response inhibition and verbal working memory.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Most researchers investigating executive functions of children with SCD focused on mental flexibility and sustained attention, overlooking other relevant frontal lobe functions such as response inhibition and planning [9][10][11][12]34]. The results of the present study failed to find support for deficits in response inhibition and verbal working memory.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition to detrimental effects on general cognitive functioning, SCD has been associated with deficits in specific areas of neurocognitive functioning including executive functioning [1,[9][10][11][12][13][14] and visuo-motor functions [15,16]. Deficits in these two areas are expected, given that silent infarcts commonly occur in frontal lobe white matter, within the border zone between the middle and anterior cerebral artery distribution [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Children with SCD and overt strokes demonstrate impairments in episodic memory (Brandling-Bennett, White, Armstrong, Christ, & DeBaun, 2003;M. J. Cohen, Branch, McKie, & Adams, 1994;Watkins et al, 1998); however, children with SCD and silent infarcts (Kugler et al, 1993;Schatz et al, 2001) were found not to differ from children with SCD without infarcts or sibling controls.…”
mentioning
confidence: 78%
“…Significantly more perseverative errors were committed on the Wisconsin Card Sorting test by children with overt strokes (Watkins et al, 1998) and children with silent infarcts made significantly more intrusion errors on a verbal learning task (Craft et al, 1993). Working memory deficits have been reported in children with silent infarcts and, in particular, those with anterior lesions (Brandling-Bennett et al, 2003). Working memory (digit span backwards) and auditory processing are impaired in children with SCD (Schatz & Roberts, 2005), and specific dysfunction in the phonological loop of the central executive also has been reported (White, Salorio, Schatz, & DeBaun, 2000).…”
mentioning
confidence: 99%
“…This literature indicates various effects related to the disease, including elevated rates of neurocognitive deficits (Armstrong et al, 1996;Schatz et al, 2002), academic or learning difficulties (Armstrong et al, 1996;Schatz et al, 2001, Schatz, 2004a, externalizing behavior disorders (Thompson et al, 2003) and depressive symptoms (Key et al, 2001). Specific cognitive deficits documented in middle childhood include sustained and selective attention, processing speed, working memory, and verbal ability (Bernaudin et al, 2000;Brandling-Bennett et al, 2003;Brown et al, 1993;Noll et al, 2001;Schatz et al, 2002Schatz et al, , 2004bSteen et al, 2005). There have been a few attempts to characterize the early development of children with SCD to better understand the pathways toward or away from these negative outcomes.…”
Section: Introductionmentioning
confidence: 99%